Peran Program Tahfidz dalam Pembinaan Karakter Religius: Relevansi Model Pembiasaan Qur’ani bagi Siswa MTs Pesantren Pembangunan Cigaru Majenang - Azka Syifaul Maula; Naeli Sangadah (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study explores the significance of Tahfidz Al-Qur’an education as a foundation for developing students’ religious character in Islamic secondary schools. Tahfidz is not merely a memorization activity but a comprehensive pedagogical process that cultivates discipline, consistency, emotional stability, and spiritual awareness. Through Qur’anic methods such as tikrār (repetition), talaqqi–tasmi’ (direct recitation to a teacher), and muroja’ah (systematic review), students experience continuous routines that strengthen their moral habits and internalize Islamic values. Supporting national data show that religious character indicators daily worship discipline, honesty, responsibility, social ethics, and love for the Qur’an are consistently higher in institutions implementing structured Tahfidz programs. The presence of teacher supervision and role modeling further enhances students’ moral development, creating an integrated system of character formation. Comparative findings from various Islamic educational institutions indicate that students involved in Tahfidz programs exhibit stronger self-control and spiritual resilience. Therefore, Tahfidz education can be considered an effective model for shaping holistic religious character and fostering.